Syndrome Evaluation System for Simultaneous Detection Pathogens Causing Acute Encephalitic Syndrome in India, Part-1: Development and Standardization of the Assay - Govekar, Sunil; Anand, Siddharth; Lakshman, Latha P.; Vasanthapuram, Ravi; Banda, Ravikumar V. (Frontiers in Medicine, 2018)
A large number of organisms are known to cause acute encephalitic syndrome (AES). A number of diagnostic tests have to be performed in order to arrive at a probable pathogen causing AES thus making it a very time consuming, laborious and expensive. The problem is further compounded by the lack of availability of sufficient volume of Cerebrospinal fluid (CSF). Thus, there is an urgent need of a diagnostic tool for the simultaneous detection of all probable pathogens responsible for causing AES. Here we report the development of a novel diagnostic method, Syndrome Evaluation System (SES) for the simultaneous detection of 22 pathogens including RNA and DNA Viruses, bacteria, fungi, and parasite all endemic to India and Southeast Asia in a single sample using a novel multiplexing strategy. Syndrome Evaluation System (SES) involves isolation of nucleic acid, multiplex amplification of the DNA, and cDNA followed by identification of the amplified product by sequence specific hybridization on SES platform with the final read out being a visually recordable colored signal. The total time required to carry out this diagnostic procedure is 7 h. The SES was standardized using the commercially available vaccines, panels and cell culture grown quantified viruses/bacteria/fungi. The limit of detection (LOD) of SES ranged between 0.1 and 50 viral particles per ml of CSF and 100 to 200 bacterial cells or 5 parasites per ml of CSF, along with 100% specificity. Precision studies carried out as per the Clinical Laboratory Improvement Amendments (CLIA) guidelines, using two concentrations of each pathogen one the LOD and the other double the LOD, clearly demonstrated, that inter/intra assay variability was within the limits prescribed by the guidelines. SES is a rapid molecular diagnostic tool for simultaneous identification of 22 etiological agents of AES encountered both in sporadic and outbreak settings.